2014
DOI: 10.3402/ljm.v9.24432
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of 16S rRNA methylase genes among β-lactamase-producing Enterobacteriaceae clinical isolates in Saudi Arabia

Abstract: BackgroundCo production of 16S rRNA methylases gene and β-Lactamase gene among Enterobacteriaceae isolates conferring resistance to both therapeutic options has serious implications for clinicians worldwide.MethodsTo study co existence of 16S rRNA methylases (armA, rmtA, rmtB, rmtC, rmtD, and npmA) and β-Lactamase (blaTEM-1, blaSHV-12, blaCTX-M-14) genes, we screened all phenotypic positive β-Lactamase producing enterobacteriaceae by polymerase chain reaction (PCR) targeting above genes. A total of 330 enterob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…In Saudi Arabia, the relationship between ESBL and 16S rRNA methyltransferase genes was investigated, and the rmtB , rmtC , and armA genes were detected in the same isolates (24). Fritsche et al analyzed gram-negative bacteria isolates from North America, Latin America, and Europe and found that the armA , rmtB , and rmtD genes were resistant to aminoglycosides in isolates with amikacin MIC values of over 128 µg/L (25).…”
Section: Discussionmentioning
confidence: 99%
“…In Saudi Arabia, the relationship between ESBL and 16S rRNA methyltransferase genes was investigated, and the rmtB , rmtC , and armA genes were detected in the same isolates (24). Fritsche et al analyzed gram-negative bacteria isolates from North America, Latin America, and Europe and found that the armA , rmtB , and rmtD genes were resistant to aminoglycosides in isolates with amikacin MIC values of over 128 µg/L (25).…”
Section: Discussionmentioning
confidence: 99%
“…Different genes reported for conferring antimicrobial resistance to various drugs were targeted: for beta-lactams (carbapenems, cephalosporins, penicillins) (bla TEM-1 , (Firoozeh et al 2012) and for efflux pumps (qnrA, qnrB, qnrS, qnrC, QnrD, AAC(6 0 )-Ib-cr, armA, rmtA, rmtB, rmtC, rmtD, npmA, qepA, qacE-sul1) (Whichard et al 2007;Ma et al 2009;Al Sheikh et al 2014;Pribul et al 2016). The primer sequences and annealing temperatures are described in Table 1.…”
Section: Detection Of Drug Resistance Genesmentioning
confidence: 99%
“…47 Of 330 unique Enterobacteriaceae clinical isolates collected at a hospital in Saudi Arabia in 2011, a total of 37% carried at least one 16S-RMTase gene. 35 …”
Section: Prevalence Of 16s Ribosomal Rna Methyltransferasesmentioning
confidence: 99%